2012
DOI: 10.1073/pnas.1206786109
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquilin-1 regulates amyloid precursor protein maturation and degradation by stimulating K63-linked polyubiquitination of lysine 688

Abstract: The pathogenesis of Alzheimer's disease (AD) is associated with proteolytic processing of the amyloid precursor protein (APP) to an amyloidogenic peptide termed Aβ. Although mutations in APP and the secretase enzymes that mediate its processing are known to result in familial forms of AD, the mechanisms underlying the more common sporadic forms of the disease are still unclear. Evidence suggests that the susceptibility of APP to amyloidogenic processing is related to its intracellular localization, and that se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
77
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(82 citation statements)
references
References 29 publications
5
77
0
Order By: Relevance
“…If APP retains high mannose forms of N-linked glycans on the cell surface, then Fbxo2 could play a role in regulating the endocytosis of APP through ubiquitination. An effect on differential trafficking of APP, namely, the retention of APP in specific cellular compartments, has been attributed to ubiquilin 1 (UBQLN1): polyubiquitination by UBQLN1 sequesters APP in the Golgi (38). Given this observation, we examined the relative distribution of APP in ER and Golgi of neurons in Fbxo2 Ϫ/Ϫ and wildtype mice and found no differences in the pattern of expression (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…If APP retains high mannose forms of N-linked glycans on the cell surface, then Fbxo2 could play a role in regulating the endocytosis of APP through ubiquitination. An effect on differential trafficking of APP, namely, the retention of APP in specific cellular compartments, has been attributed to ubiquilin 1 (UBQLN1): polyubiquitination by UBQLN1 sequesters APP in the Golgi (38). Given this observation, we examined the relative distribution of APP in ER and Golgi of neurons in Fbxo2 Ϫ/Ϫ and wildtype mice and found no differences in the pattern of expression (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…This prevented APP maturation and trafficking to the plasma membrane and subsequent proteolytic processing. Ubiquilin-1 was shown to mediate these effects by stimulating K63-linked polyubiquitination of APP-Lys688 [21]. In summary, these in vitro data altogether suggest that ubiquilin-1 functions as an important molecular chaperone for APP, which regulates APP trafficking, maturation, levels and processing.…”
Section: Genetic Association Of Ubqln1 With Admentioning
confidence: 86%
“…The reasons for these contradicting findings are not completely clear, but one explanation could be that ubiquilin-1-mediated regulation of APP may be different in diverse cell types. Nevertheless, recent studies have confirmed that ubiquilin-1 influences Ab production by directly interacting with APP rather than by modulating secretase function [20,21], further underscoring an important role for ubiquilin-1 in the regulation of APP levels. The recent interesting pieces of data demonstrate that ubiquilin-1 levels are diminished in human AD brain and that RNAi-mediated knockdown of ubiquilin-1 resulted in enhanced production of Ab and subsequently increased neuronal cell death, substantiating the initial findings [20,21].…”
Section: Genetic Association Of Ubqln1 With Admentioning
confidence: 93%
See 2 more Smart Citations